Diethylamine-catalyzed environmentally benign synthesis of 1-oxo-hexahydroxanthenes and bis-coumarins at ambient temperature - Kupwade, Ravindra V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (Research on Chemical Intermediates, 2016)
An extremely simple, economical and environmentally benign protocol has been described for one-pot synthesis of 1-oxo-hexahydroxanthenes by pseudo three-component condensation between salicylaldehydes and dimedone, cyclohexane-1,3dione or 5-methyl cyclohexane-1,3-dione using diethylamine as the catalyst. Based upon the mechanism of the reaction, the protocol has been extended towards the synthesis of tetraketones and bis-coumarins.